Low-temperature catalytic CO2 dry reforming of methane on Ni-based catalysts: A review - Wang, Ye; Yao, Lu; Wang, Shenghong; Mao, Dehua; Hu, Changwei (Fuel processing technology, 2018)
CO2 dry reforming of methane (DRM) not only utilized the two greenhouse gases, CO2 and CH4, but also produced synthesis gas, which could be used for Fischer-Tropsch synthesis. Besides, DRM reaction could utilize marsh gas and the gaseous products from pyrolysis of biomass, consequently increasing their value for businesses and reducing environment pollution, thereby providing ways for sustainable development. Nickel based catalyst was widely used in DRM reaction. This paper reviewed the recent progresses of the DRM reaction at low temperature. Suitable supports and promoters improved the catalytic performance by adjusting the interaction between nickel and the support. Besides, the temperature of calcination, the order of materials loading on support, the reduction temperature, and the nickel particle size also altered the performance of the catalysts. It was suggested that by investigating the interaction of supports, promoters with nickel, as well as their structural adjustment, the development of low temperature DRM catalysts was feasible. The scheme of CO2 dry reforming of methane. [Display omitted] •New low temperature (<600°C) DRM catalysts are important.•Alkaline earth supports enhances the catalytic performance.•Rare earth promoters contribute to the formation of new active phase.•The atomic level essence of nickel-based active phase needs more investigations.